Does large NGS panel analysed using exome tumour sequencing improve the management of advanced non-small-cell lung cancers?. (November 2021) - Niogret, Julie; Dalens, Lorraine; Truntzer, Caroline; Chevrier, Sandy; Favier, Laure; Lagrange, Aurélie; Coudert, Bruno; Fraisse, Cléa; Foucher, Pascal; Zouak, Ayoub; Westeel, Virginie; Goussot, Vincent; et al.
Highlights: Large Next Generation Sequencing (LNGS) is feasible in routine practice. LNGS identified at least one potential molecular target in 74.4% of patients. LNGS do not appear to provide clinical benefit to patients with advanced Non-Small-Cell lung Cancers (NSCLC). LNGS is a complement of routine molecular biology in search of uncommon mutations. Abstract: Introduction: Non-small-cell lung cancer (NSCLC) is one of the most common and deadly cancers. Several molecular drivers of oncogene addiction are now known to be strong predictive biomarkers for target therapies. Advances in large Next Generation Sequencing (LNGS) have improved the ability to detect potentially targetable mutations. However, the integration of LNGS into clinical management in an individualized manner remains challenging. Methods: In this single-center observational study we included all patients with advanced NSCLC who underwent LNGS. Somatic and germline exome analysis was performed with a restriction on 323 cancer related genes. Variants were classified and Molecular Tumour Board (MTB) made therapeutic propositions. Results: We performed LNGS analysis in 281 patients with advanced NSCLC between March 2015 and January 2018. Technical failure occurred in only 3% of cases. Three hundred and fifty-six targetable mutations were detected. At least one targetable mutation was found in 209 patients. For all these patients, the MTB was able to recommend treatment with a targeted agent based on the evaluation of the tumour's genetic profile and treatment history. Twenty-nine patients (13.9%) were subsequently treated with an MTB-recommended targeted therapy. We did not observe any improvement in terms of clinical benefit for these patients. Conclusions: In this case series, we show that including LNGS into routine clinical management was feasible but does not appear to provide clinical benefit in the management of patients with advanced NSCLC.